THE EFFECT OF USING “PICTURE WORD INDUCTIVE MODEL (PWIM)” ON STUDENTS’ VOCABULARY MASTERY - Yasin, Riesky Ramadhani; Noni, Nurdin; Korompot, Chairil Anwar (JTechLP: Journal of Technology in Language Pedagogy, 2022)
The purpose of this research is to know the effect of using the “Picture Word Inductive Model (PWIM)” on students’ vocabulary mastery. The method used in this research is pre-experiment with one group pretest-posttest. The population in this study were students of class VIII at SMP Negeri 28 Makassar for the 2022/2023 academic year. This research used a cluster random sampling technique. The sample of this research was class VIII A, which consisted of 20 students. The instrument used in this research was a vocabulary test. The results of this study, the mean score of students' pretest and posttest was increased (64.80 to 86.05). The standard deviation score for the pretest (17.59) and posttest (9.53), showed that the standard deviation of the posttest was smaller than the standard deviation of the pretest. The result of statistical hypothesis testing by using sample t-test found that (Sig < α (0.05)), Therefore, Ho was rejected and H1 was accepted, which means that the use of the Picture Word Inductive Model (PWIM) can improve students' vocabulary mastery.